The optimization of hydrothermal synthesis of MnxCo3‐xO4/GC catalyst for low temperature NH3‐SCR /using design of experiments. Issue 10 (6th August 2021) - Ko, Songjin; Tang, Xiaolong; Gao, Fengyu; Zhou, Yuansong; Zhang, Runcao; Liu, Yuanyuan; Liu, Hengheng
Abstract: BACKGROUND: In this study, a new catalyst for low‐temperature selective catalytic reduction of NOx with NH3 (NH3 ‐SCR) were prepared by using glucose and discussed optimization of the synthetic conditions of Mnx Co3−x O4 /GC (glucose carbon) catalysts by using the design of the experiments. A response surface methodology (RSM) combined with the central composite design (CCD) was applied to model and optimize the synthetic conditions. RESULTS: As a result, the optimum NOx conversion of 95.6% and N2 selectivity of 81.8% were obtained at Mn/Co 2.1, urea/(Mn + Co) mole ratio 11.5, glucose/(Mn + Co) mole ratio 8.9, preparation temperature 175.4 ° C, and calcination temperature 376.3 ° C . The SEM (Scanning electron microscope) image and EDS (Energy Dispersive Spectroscopy) analysis showed that metal oxides of Mn and Co were uniformly accumulated on the carbon microsphere surface. XRD (X‐ray diffraction) patterns showed that CoCo2 O4 content in the catalyst increased with the increase of the glucose/(Mn + Co) mole ratio, which reduced the interaction between Mn and Co, and played a negative impact on catalytic performance. FTIR (Fourier‐transform infrared) spectra showed that the catalyst surface in the optimum preparation conditions had more oxygen‐containing functional groups and that the excessive glucose carbon was unfavourable to catalytic performance. For urea/(Mn + Co), as urea/(Mn + Co) decreased, in addition to the decrease in Mn and Co content in the catalyst due to the decrease in precipitant, CoCo2 O4 content in the catalyst also increased and oxygen‐containing functional groups decreased, both of which resulted in the decrease of the catalytic performance. CONCLUSION: The H2 ‐TPR and NH3 ‐TPD results demonstrated that the catalyst prepared in the optimum conditions possessed a stronger reducing ability, more acid sites, and stronger acid strength than the other. © 2021 Society of Chemical Industry